1991
DOI: 10.1116/1.585208
|View full text |Cite
|
Sign up to set email alerts
|

Ordered arrays of proteins on graphite observed by scanning tunneling microscopy

Abstract: Two globular proteins, lysozyme and chymotrypsinogen A, were imaged on graphite using a scanning tunneling microscope. In contrast to the isolated molecules typically seen, long-range order was observed in both of these systems when the protein concentration of the solution deposited on the graphite was sufficient for multilayer coverage. For lysozyme, regular two-dimensional arrays of protein molecules were seen, with periodicities ranging from about 40 (the approximate size of a lysozyme molecule) to about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…This was the standard calibration procedure to test the tips in our STM measurements. The STM image of H 3 -PMo 12 O 40 deposited on HOPG is shown in Figure 2a and clearly indicates the formation of an ordered structure on the surface. difference in the sizes of the cations leads to differences in the lattice constants of these materials 25 Acidic protons, water of crystallization, and cations exist in the interstices between polyanions in the solid state as shown schematically in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was the standard calibration procedure to test the tips in our STM measurements. The STM image of H 3 -PMo 12 O 40 deposited on HOPG is shown in Figure 2a and clearly indicates the formation of an ordered structure on the surface. difference in the sizes of the cations leads to differences in the lattice constants of these materials 25 Acidic protons, water of crystallization, and cations exist in the interstices between polyanions in the solid state as shown schematically in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…31 It has been found that when the identity of the countercation of the heteropoly anion (12-molybdophosphate) is fixed and the extent of exchange is varied, the oxidation activity for methacrolein varies significantly in a manner that is distinctly different from the acidity of the catalyst measured by means of the adsorption of NH 3 . 28 The reducibilities of salts of 12-molybdophosphoric acid, M x/n H 3-x PMo 12 O 40 (where M is an n-valent cation), were measured by Ai in a closed system using H 2 . 3 The temperature at which H 2 consumption reached 0.3 mol per mole of 12-molybdophosphoric acid (denoted as "the reduction temperature") was employed as the index of reducibility.…”
Section: Effect Of Countercation On Ndrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in fact the cleaved HOPG surface exhibits hydrophobic property and is not beneficial for hydrophilic organic and biological materials to combine with it. Only few kinds of proteins, such as lysozyme and chymotrypsinogen A, can be dispersed uniformly and adsorbed orderly on HOPG surface [34]. In our preliminary experiments, catalase was directly deposited onto a freshly cleaved HOPG.…”
Section: Stm Image Of Catalase On Freshly Cleaved Hopg Surfacementioning
confidence: 99%
“…Further, the amount of adsorbed enzyme increases with the acidic conditions. 12 Previously, densely packed lysozyme molecules were observed in molecular-resolution STM images. Under high-surface-pressure conditions, formation of the same type of assembled structure is predicted.…”
mentioning
confidence: 99%